2017
DOI: 10.1007/s00221-017-4977-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of molecular marker expression in early zebrafish brain development following chronic ethanol or morpholino treatment

Abstract: This study was undertaken to ascertain whether defined markers of early zebrafish brain development are affected by chronic ethanol exposure or morpholino knockdown of agrin, sonic hedgehog, retinoic acid and fibroblast growth factors, four signaling molecules that are suggested to be ethanol sensitive. Zebrafish embryos were exposed to 2% ethanol from 6–24 hpf or injected with agrin, shha, aldh1a3 or fgf8a morpholinos. In situ hybridization was employed to analyze otx2, pax6a, epha4a, krx20, pax2a, fgf8a, wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In the context of mammalian blood alcohol content (BAC), a media ethanol concentration of 171–342mM corresponds to embryonic tissue BACs of 0.20–0.40 g/dL, which are levels within the biological tolerance of humans. Moreover, the ethanol exposure concentrations used in our study are within range of concentrations used in several other FASD zebrafish studies (Joya, Garcia-Algar, Vall, & Pujades, 2014; Kalueff, Stewart, & Gerlai, 2014; Pan, Kaiguo, Razak, Westwood, & Gerlai, 2011; Sylvain, Brewster, & Ali, 2011; Yin et al, 2014; Zhang, Boa-Amponsem, & Cole, 2017; Zhang et al, 2014; Zhang, Ojiaku, & Cole, 2013).…”
Section: Methodsmentioning
confidence: 55%
“…In the context of mammalian blood alcohol content (BAC), a media ethanol concentration of 171–342mM corresponds to embryonic tissue BACs of 0.20–0.40 g/dL, which are levels within the biological tolerance of humans. Moreover, the ethanol exposure concentrations used in our study are within range of concentrations used in several other FASD zebrafish studies (Joya, Garcia-Algar, Vall, & Pujades, 2014; Kalueff, Stewart, & Gerlai, 2014; Pan, Kaiguo, Razak, Westwood, & Gerlai, 2011; Sylvain, Brewster, & Ali, 2011; Yin et al, 2014; Zhang, Boa-Amponsem, & Cole, 2017; Zhang et al, 2014; Zhang, Ojiaku, & Cole, 2013).…”
Section: Methodsmentioning
confidence: 55%
“…However, recent studies using a similar ethanol exposure (2% from 6-24 hpf), found relatively minor alterations to the pattern of molecular markers of the brain (Zhang et al 2017). The patterning of the forebrain, (based on otx2 and pax6a expression) midbrain (based on fgf8a, wnt1 and pax2a), and hindbrain (based on pax6a, epha4 and, krox20) appeared largely normal, with the exception of the expression of epha4a in the rhombomere 1 boundary (Zhang et al 2017). The expression of oxt:EGFP sensitive time window is from 4-5 dpf.…”
Section: R a F Tmentioning
confidence: 92%
“…In addition to the defects in neurotransmitter systems following developmental exposure to ethanol, further alterations in brain development exist. These include altered morphology of the midbrain-hindbrain boundary (MHB), reduced expression of pax6a in the eye ( Zhang et al, 2017 ), forebrain, and hindbrain, as well as reduced expression of epha4a in rhombomere 1 of the hindbrain, which point towards altered brain development, including cerebellar development resulting from ethanol exposure. Further, early ethanol exposure has been shown to contribute to altered neurogenesis during early zebrafish development.…”
Section: Prenatal Stressmentioning
confidence: 99%